ChemInform Abstract: Ti(III)‐Catalyzed Cyclizations of Ketoepoxypolyprenes: Control over the Number of Rings and Unexpected Stereoselectivities. Issue 48 (2nd December 2014) - Morcillo, Sara P.; Miguel, Delia; Resa, Sandra; Martin‐Lasanta, Ana; Millan, Alba; Choquesillo‐Lazarte, Duane; Garcia‐Ruiz, Juan M.; Mota, Antonio J.; Justicia, Jose; Cuerva, Juan M.
Abstract Several synthetic applications of the primary reaction products are described.